Pengaruh Beban Kerja dan Kompensasi Terhadap Kinerja Guru - Bonse Aris Mandala Putra Simangunsong (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
SMA "X" is an educational institution that carries the mission to build quality human qualities through formal education. However, schools often face obstacles related to teacher performance as one of the key drivers of educational success. Workload and compensation are two factors that can affect performance. Regarding this phenomenon, this study aims to determine the effect of workload and compensation on teacher performance in "X" high schools, both partially and simultaneously. Data collection was conducted on the overall population of existing subject teachers. The research method used is descriptive and verification methods. The analysis in this study was carried out using multiple linear regression. Based on the results of hypothesis testing, it is evident that the workload and compensation each has a positive and significant effect on the performance of subject teachers in "X" high schools. Simultaneously, workload and compensation also positively influence fan significant.